Embodiment of twenty-first century zeitgeist in Chick Lit - Abu Ujum, Diana (2017)
Chick Lit, a particular genre of popfiction known as ‘postfeminist fiction’, provides an excellent avenue or stage for the discussion of the zeitgeist. This is the same zeitgeist that has been credited with respect to Chick Lit’s popularity but never explicitly defined. There is a need to discover what the zeitgeist is in connection to Chick Lit and in turn, learn how it permeates this particular type of fiction, making Chick Lit a distinguishable brand of narrative form. The study of the genre through the usage of a new methodological tool can provide insight into the dimensions of popular fiction’s plot constructions. Chick Lit is rich with new interpretations of the ideology of women to date as it tells the story of contemporary women by women for women readers. The most transparent way to study these new interpretations is to study female protagonists or ‘postfeminist heroine’ of Chick Lit novels and their character development. Ultimately, based on the depiction of changing times and the utilisation of certain real spaces (whether geographical or domain-based) that exist in Chick Lit novels, the question of what the zeitgeist truly is becomes important to answer to better define Chick Lit’s value as a literary genre. The study perhaps can lend more sociological import to postfeminism, and relate the significance of Chick Lit’s narrative form and its potential. For these reasons, three best-selling Chick Lit novels are analysed as a narrative form that serve as a social commentary of the times. The research includes an examination of the plot constructions that allow for the development of postfeminist heroine’s character traits to take place. The point of departure for this study is Scott McCracken’s book on pulp fiction, highlighting that the study of popular fiction can still inform us of our identity and the social environment we live in. As McCracken points out, the study of popular fiction needs to be done in a more holistic fashion instead of in isolation. Keeping this in mind, I have applied a novel method by introducing a social network theory (Social Focus Theory) as a tool to determine the character development of the protagonist that is dependent upon the movement of the plot structure that uses the zeitgeist as a plot device. Upon determining the social foci that appear based on selected characters’interactions, I have been able to trace character development and plot evolution from the existing network found within these novels and gauge the thematic parallels to these specific literary elements. The most exciting result of the research is the discovery that basic social network analysis can be utilised to dissect and explicate literature. Since Chick Lit is controversially known for being criticised for its questionable literariness, the study provides justification for the genre’s potential contribution to literary analysis.